Electrifying the fence or living with consequences? Problem animal control threatens the long‐term viability of a free‐ranging lion population - Trinkel, M.; Fleischmann, P. H.; Slotow, R. (Journal of zoology (1987), 2017)
A fundamental problem in conserving large carnivores is habitat destruction, which results in patchy, isolated protected areas. In addition, human–wildlife conflict along reserve borders negatively affects carnivore populations throughout protected reserves. We present pride composition of nine lion prides and lion mortalities on bordering farmland over a 17‐year study in Etosha National Park, Namibia. Although Etosha National Park is fully fenced, lions can – due to poor maintenance of the fence – move freely onto bordering farmland. Conflict with humans caused 48% of mortalities among subadult and adult lions. Most animals killed by humans consisted of subadult males and adult females: 59% of subadult males and 27% of adult females were shot or poisoned along the border of Etosha National Park. The disproportional high killing of subadult males on farmland affected the tenure periods of resident male coalitions. Probably due to a lack of competition from maturing subadult males, adult males held tenure over prides for nearly 7 years, about three times longer compared to other ecosystems, which increases the risk of inbreeding in this population. Such unregulated and unplanned selective mortality may be more widespread, and managers should monitor for negative effects, especially in socially complex species. A fundamental problem in conserving large carnivores is habitat destruction, which results in patchy, isolated protected areas. In addition, human wildlife conflict along reserve borders negatively affects carnivore populations throughout protected reserves. We present pride composition of nine lion prides and lion mortalities on bordering farmland over a 17‐year study in Etosha National Park, Namibia. Although Etosha National Park is fully fenced, lions can – due to poor maintenance of the fence ‐ move freely onto bordering farmland. Conflict with humans caused 48% of mortalities amongst subadult and adult lions, consisting mostly of subadult males and adult females. The disproportionally high killing of subadult males on farmland affected the tenure periods of resident male coalitions. Probably due to a lack of competition from maturing subadult males, adult males held tenure over prides for nearly 7 years, about three times longer compared to other ecosystems, which increases the risk of inbreeding.